Cerebral Cavernous Malformation: From Mechanism to Therapy. Issue 1 (25th June 2021) - Snellings, Daniel A.; Hong, Courtney C.; Ren, Aileen A.; Lopez-Ramirez, Miguel A.; Girard, Romuald; Srinath, Abhinav; Marchuk, Douglas A.; Ginsberg, Mark H.; Awad, Issam A.; Kahn, Mark L.
Abstract : Cerebral cavernous malformations are acquired vascular anomalies that constitute a common cause of central nervous system hemorrhage and stroke. The past 2 decades have seen a remarkable increase in our understanding of the pathogenesis of this vascular disease. This new knowledge spans genetic causes of sporadic and familial forms of the disease, molecular signaling changes in vascular endothelial cells that underlie the disease, unexpectedly strong environmental effects on disease pathogenesis, and drivers of disease end points such as hemorrhage. These novel insights are the integrated product of human clinical studies, human genetic studies, studies in mouse and zebrafish genetic models, and basic molecular and cellular studies. This review addresses the genetic and molecular underpinnings of cerebral cavernous malformation disease, the mechanisms that lead to lesion hemorrhage, and emerging biomarkers and therapies for clinical treatment of cerebral cavernous malformation disease. It may also serve as an example for how focused basic and clinical investigation and emerging technologies can rapidly unravel a complex disease mechanism.